PREDICTION OF TITANIUM ALLOYS EROSIVE WEAR UNDER LONG-TERM DROPLET-IMPACT EFFECT - Valery N. Varavka; Oleg V. Kudryakov; Alexey F. Mednikov (Advanced Engineering Research, 2011)
The approximating model for the definition of the steam turbines blades wear rate under the continuous operation through the droplet-impact erosion is built on the ground of the comparative analysis of the stand test data of the titanium alloy samples.